Effect of filler characteristics on radiopacity of experimental nanocomposite series*. Issue 14 (18th July 2018) - Marghalani, Hanadi Yousif
Abstract: This study evaluated the radiopacity of experimental nanocomposites and compared the values to those of human's enamel and dentin. Three disc-shape (6 mm diameter × 1 mm thickness) specimens of each eleven nanocomposite series based on different filler particle size formulations (range of 100–1500 nm) and two shapes (spherical and irregular) were prepared in a split Teflon mold. After irradiation by a halogen light, the series were digitally radiographed (Kodak Unit imaging) along with 99.5% Aluminum step-wedge. The radiographic density in Mean Gray Values were measured, and then converted into Al (Aluminum) equivalent (mm). The data were analyzed by one-way ANOVA, Tukey's HSD post hoc test and independent t-test ( α  = 0 . 05). The radiopacity values varied among the nanocomposite series ( p  < 0.05). The highest mean Al equivalent was recorded in bi-modal irregular-shape series, I-450/1000 (RZD 111) (2.74 ± 0.41) followed by monomodal irregular-shape, I-450 (RZD 103) (2.31 ± 0.43). The lowest value was expressed by monomodal spherical-shape larger size filler series, S-1000 (RZD 105) (0.12 ± 0.02). The irregular-shape series showed more radiopacities than the spherical-shape series in a range equivalent to those of enamel and dentin. The regression analysis demonstrated a decrease in the radiopacity values with increasing filler particle size of both spherical and irregular-shape monomodal series. The shape and composition of nanofillers have an effect on radiopacity of the experimental series.